Increased autophagy in CD4+ T cells of rheumatoid arthritis patients results in T‐cell hyperactivation and apoptosis resistance. Issue 12 (5th October 2016) - van Loosdregt, Jorg; Rossetti, Maura; Spreafico, Roberto; Moshref, Maryam; Olmer, Merissa; Williams, Gary W.; Kumar, Pavanish; Copeland, Dana; Pischel, Ken; Lotz, Martin; Albani, Salvatore
Abstract : The autophagic flux was demonstrated to be increased in T cells from patients with rheumatoid arthritis, resulting in increased T‐cell activation and apoptosis resistance. Autophagy inhibition using hydroxychloroquine in primary patient cells restored T‐cell homeostasis and apoptosis sensitivity. Abstract : Rheumatoid arthritis (RA) is an autoimmune disease hallmarked by aberrant cellular homeostasis, resulting in hyperactive CD4 + T cells that are more resistant to apoptosis. Both hyperactivation and resistance to apoptosis may contribute to the pathogenicity of CD4 + T cells in the autoimmune process. A better knowledge of the mechanisms determining such impaired homeostasis could contribute significantly to both the understanding and the treatment of the disease. Here we investigated whether autophagy, is dysregulated in CD4 + T cells of RA patients, resulting in disturbed T‐cell homeostasis. We demonstrate that the rate of autophagy is significantly increased in CD4 + T cells from RA patients, and that increased autophagy is also a feature of in vitro activated CD4 + T cells. The increased apoptosis resistance observed in CD4 + T cells from RA patients was significantly reversed upon autophagy inhibition. These mechanisms may contribute to RA pathogenesis, as autophagy inhibition reduced both arthritis incidence and disease severity in a mouse collagen induced arthritis mouse model. Conversely, in Atg5 flox/flox ‐CD4‐Cre + mice, in which all T cells are autophagy deficient, T cells showed impaired activation and proliferation. These data provide novel insight into the pathogenesis of RA and underscore the relevance of autophagy as a promising therapeutic target.